2003
DOI: 10.1243/095440503762502279
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of in-process cutting constants in ball-end milling

Abstract: Two methods are presented for the estimation of tangential, radial and axial cutting coefficients for the shearing and ploughing mechanisms from a single set of cutting forces in ball-end milling. These estimation methods are based upon the invertibility of the analytical milling force model, which considers both the shearing and the ploughing mechanisms by incorporating their respective cutting constants in the local force model. The periodic milling forces are established as the convolution integral of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The analytical force model presented by Wang and Zheng [17] has shown that the total milling force is the output of the convolution integration process involving the local cutting force model in Eq. 5 and the geometrical Fig.…”
Section: The Shearing and Ploughing Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical force model presented by Wang and Zheng [17] has shown that the total milling force is the output of the convolution integration process involving the local cutting force model in Eq. 5 and the geometrical Fig.…”
Section: The Shearing and Ploughing Constantsmentioning
confidence: 99%
“…Hence, the complete ball end is submerged and engaged in the cutting process. Six cutting constants for each milling experiment are identified based on the method presented in Wang and Zheng [17]. To illustrate the validity of the identified cutting constants, the simulated milling forces are reconstructed using the six identified cutting constants.…”
Section: Shearing and Ploughing Cutting Constantsmentioning
confidence: 99%
“…Earlier works on the establishment of the dualmechanism cutting constants have been based on the orthogonal cutting test data [7]; this test data is then transformed to the cutting constants for a ball end cutter according to its cutting edge geometry. Based on the analytical milling force model, recent works have shown that these cutting constants can be conveniently identified from the average forces of two cutting tests in [8,9] and estimated online from the forces of a single cutting test for a cylindrical end mill in [10] and for a ball end mill in [11]. This online identification of cutting constants make possible the real-time monitoring of the milling process by making available to the user the detailed information about both the shearing and the ploughing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Cutting conditions that render T a1 singular and should be avoided have been discussed in [10] and [11], where it was shown that Eq. 15 is not applicable for a slot milling condition for the cylindrical or ball end cutters with flute numbers larger than 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation